Revitalization of Collection Development for Learning Effectiveness in the School Library of SMK Harapan 2 Rancaekek - et. al., Haria Saputry Wahyuni S.IPus., M.I.Kom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Based on the regulations stipulated by the Head of PERPUSNAS (National Library) of the Republic of Indonesia number 12 of 2017 regarding SMA library standards (Senior High School), there are six library standard scopes that must be owned. Library collections are the first thing that must be fulfilled in meeting library standards. From a visit to SMK Harapan 2 Rancaekek, the types of library materials in the library are only basic textbooks (school packages), there are no other supporting books such as novels, periodicals, educational media, and multi-media props. Schools as facilitators must meet the needs of students in meeting the information needs for learning. The purpose of this research is to find out how to revitalize the school library in supporting the effectiveness of learning. The method used in data collection using descriptive qualitative methods. The analysis technique used is the Miles and Huberman technique. The results of this study indicate that the revitalization of the library is still in the process stage because the librarian on duty is still relatively new. With the PKM carried out by a team of lecturers from the Library and Information Science study program, the desired hope is to achieve a library that is in accordance with the National Standards from the regulations of the Head of the National Library in order to support student learning effectiveness.